CO2 Uptake Model of Biomass Silica Foamed Concrete - Lee, Yee Loon; Koh, Heng Boon; Abdul Karim, Ahmad Tarmizi; Wimala, Mia; Ng, C. (International Journal of Integrated Engineering, 2010)
The cement industry contributes about 5% to global anthropogenic CO2 emissions. CO2 isemitted from the calcination process of limestone, from combustion of fuels in the kiln, aswell as from power generation. A model of CO2 uptake by biomass silica foamed concrete isproposed as a potential mitigation strategy against CO2-emission. The key parameters in thecement production process are defined and the total CO2 emissions are reviewed. Acomparison between CO2 emission and CO2 uptake by carbonation is made. The forecastingof CO2 uptake by carbonation is modeled with the use of Microsoft Excel. The CO2 emissionmitigation options are discussed based on the modeling on CO2 uptake by biomass silicafoamed concrete. The proposed foamed concrete absorbs CO2 42.7% faster than the normalPortland cement concrete, with a regression accuracy of 0.98. Successful deployment couldcontribute towards sustainable development while benefiting from the carbon credits.